Е-наука на шляху до семантичного Грід. Частина 2: Семантичний Web-І семантичний Грід - Zgurovsky, M. Z.; Petrenko, A. І. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
The semantic Web, based on metadata, ontology, and software agents, is investigated as a foundation for the semantic Grid, in which information and services have clear determination, which gives computers and people the possibility to cooperate rather with knowledge than with information (as that is done at present). Approaches to ontology and Web- and Grid-services with and without state, their cooperation, architecture, and the existent realizations of the semantic Grid are considered.